A lithium ion/oxygen hybrid battery with high energy and high power. Issue 58 (4th July 2018) - Mu, Shijia; Zhu, Ding; Zhang, Ruixue; Zhang, Kaifang; Ding, Zhendong; Chen, Yungui
Abstract : A high-energy and high-power lithium ion/oxygen hybrid battery system. Abstract : A novel lithium ion/oxygen hybrid battery system is proposed that uses the advantages and minimizes the disadvantages of both lithium-ion batteries (LIBs) and lithium-oxygen batteries (LOBs). In it, the LOB-part plays range-extending and high-power output roles, while using the discharge-priority of the LIB-part is suggested to compensate the cycling-life shortcomings of the LOB-part.